2011
DOI: 10.1007/s00709-011-0314-1
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of salt stress in lemongrass by salicylic acid

Abstract: Soil salinity is one of the key factors adversely affecting the growth, yield, and quality of crops. A pot study was conducted to find out whether exogenous application of salicylic acid could ameliorate the adverse effect of salinity in lemongrass (Cymbopogon flexuosus Steud. Wats.). Two Cymbopogon varieties, Krishna and Neema, were used in the study. Three salinity levels, viz, 50, 100, and 150 mM of NaCl, were applied to 30-day-old plants. Salicylic acid (SA) was applied as foliar spray at 10(-5) M concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 49 publications
2
23
1
Order By: Relevance
“…Moreover, many previous studies have shown that SA plays a role in many biotic and abiotic stresses (Vicente and Plasencia, 2011). This phytohormone can regulate responses to salinity (Idrees et al, 2012) and cold (Siboza et al, 2014), drought (Shen et al, 2014) and the toxicity of heavy metals (Tamás et al, 2015). Moreover, research has shown that SA levels and/or SA signaling played a positive regulatory role in plant response to polyethylene glycol (PEG)-simulated drought stress (He et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many previous studies have shown that SA plays a role in many biotic and abiotic stresses (Vicente and Plasencia, 2011). This phytohormone can regulate responses to salinity (Idrees et al, 2012) and cold (Siboza et al, 2014), drought (Shen et al, 2014) and the toxicity of heavy metals (Tamás et al, 2015). Moreover, research has shown that SA levels and/or SA signaling played a positive regulatory role in plant response to polyethylene glycol (PEG)-simulated drought stress (He et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They also mentioned chlorophyll reduction could be caused by pigment destruction, instability, and syn thesis reduction by salinity stress. Idrees et al [19] observed that chlorophylls showed the greatest loss compared to carotenoids in lemongrass plants by NaCl effects, when only salinity stress was applied; however, when SA treatments with NaCl were added, negative effects decreased. The beneficial effects of SA on photosynthetic compounds were considered by stimulation on Rubisco [16].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years some authors have reported the pos itive effects of SA against the negative effects of NaCl [4,5,7,16,19,[24][25][26], because SA induced directly or indirectly plant antioxidant compounds and enzymes, such as SOD, CAT, and POX, to protect the plants and prevent oxidative stress [4,26,27]. In fact, SA up regulated POX genes in plants under stress con ditions [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations